Internationalization Process Of Firms From Developing Country:An Empirical Evidence Of UAE Family Business Firms - Ahamat, Amiruddin; Shahkat Ali, Muhamad Sham (OCERINT International Organization Center of Academic Research, 2018)
There are many reasons behind the internationalization expansion of family businesses.This study provides an understanding of the international expansion strategy of family businesses in the United Arab Emirates (UAE) in comparison to other countries.The purpose of this paper is to investigate the internationalization strategy for family businesses,key driving factors and the major barriers that could restrict United Arab Emirates family businesses progress.Based on the objective of the study, this paper encompasses both qualitative and quantitative research.The sample of this study includes 20 managers of top 10 family businesses in UAE.The findings indicate that most of the participants (80%) are interested in the internationalization process to expand their operations. To remain competitive,UAE policymakers should consider entrepreneurship education and business initiative to stimulate entrepreneurship activities both at the local and national levels.